Modulation of the Mesenchymal Stem Cell Secretome Using Computer-Controlled Bioreactors: Impact on Neuronal Cell Proliferation, Survival and Differentiation - Teixeira, Fábio G. (Sci Rep, 2016)
In recent years it has been shown that the therapeutic benefits of human mesenchymal stem/stromal cells (hMSCs) in the Central Nervous System (CNS) are mainly attributed to their secretome. The implementation of computer-controlled suspension bioreactors has shown to be a viable route for the expansion of these cells to large numbers. As hMSCs actively respond to their culture environment, there is the hypothesis that one can modulate its secretome through their use. Herein, we present data indicating that the use of computer-controlled suspension bioreactors enhanced the neuroregulatory profile of hMSCs secretome. Indeed, higher levels of in vitro neuronal differentiation and NOTCH1 expression in human neural progenitor cells (hNPCs) were observed when these cells were incubated with the secretome of dynamically cultured hMSCs. A similar trend was also observed in the hippocampal dentate gyrus (DG) of rat brains where, upon injection, an enhanced neuronal and astrocytic survival and differentiation, was observed. Proteomic analysis also revealed that the dynamic culturing of hMSCs increased the secretion of several neuroregulatory molecules and miRNAs present in hMSCs secretome. In summary, the appropriate use of dynamic culture conditions can represent an important asset for the development of future neuro-regenerative strategies involving the use of hMSCs secretome.